Olefin Metathesis: Life, Death, and Sustainability - Lummiss, Justin Alexander MacDonald (Université d'Ottawa / University of Ottawa, 2015)
Over the past 15 years, ruthenium-catalyzed olefin metathesis has emerged as a cornerstone synthetic methodology in academia. Applications in fine-chemicals and pharmaceutical manufacturing, however, are just beginning to come on stream. Industrial uptake has been impeded by economic constraints associated with catalyst costs. These are due both to direct costs (exacerbated by intellectual property issues), and to further pressure exerted by the low turnover numbers attainable, and the need for extensive purification to remove ruthenium residues. From another perspective, however, these difficulties can be seen as arising from our rudimentary understanding of the fundamental organometallic chemistry of the Ru=CHR bond. In particular, we know little about the nature and reaction pathways of the Ru-methylidene unit present in the active species that propagates metathesis, and in the catalyst resting state. We know slightly more about the ruthenacyclobutane species, but still too little to guide us as to their non-metathetical reaction pathways, their contribution to deactivation relative to the methylidene species, and potential work-arounds. This thesis work was aimed at improving our understanding of the reactivity, speciation, and decomposition of key ruthenium intermediates in olefin metathesis. A major focus was the behaviour and deactivation of species formed from the second-generation Grubbs catalyst RuCl2(H2IMes)(PCy3)(=CHPh) (S-GII), which dominates ring-closing metathesis. Also studied were derivatives of the corresponding IMes catalyst A-GIIm, containing an unsaturated Nheterocyclic carbene (NHC) ligand. The methylidene complexes RuCl2(NHC)(PCy3)(=CH2) (GIIm) represent the resting state of the catalyst during ring-closing and cross-metathesis reactions: that is, the majority Ru species present during catalysis. Mechanistic studies of these key intermediates have been restricted, however, by the low yields and purity with which they could be accessed. Initial work therefore focused on designing a clean, high-yield route to the second-generation Grubbs methylidene complexes S-GIIm and A-GIIm. These routes were subsequently expanded to develop access to isotopically-labelled derivatives. Locating a 13C-label at the key alkylidene site, in particular, offers a powerful means of tracking the fate of the methylidene moiety during catalyst deactivation. Access to GIIm enabled detailed studies of the behaviour and decomposition of the Grubbs catalysts. First, the long-standing question of the impact of saturation of the NHC backbone (i.e. IMes vs. H2IMes) was examined. Dramatic differences in the behaviour of the two complexes were traced to profound differences in PCy3 lability arising from the diminished π-acidity of the IMes ligand. Secondly, the vulnerability of GIIm to nucleophiles was examined. This is an important issue from the perspective of decomposition by adventitious nucleophiles in the reaction medium during catalysis, but also reflects on substrate scope. For amine additives, the dominant deactivation pathway was shown to typically involve attack on the resting-state methylidene complex, not the metallacyclobutane, which has often been regarded as the most vulnerable intermediate. In addition, the sigma-alkyl intermediate formed by nucleophilic attack of displaced phosphine at the methylidene carbon was trapped by moving to the first-generation complex, and using a nitrogen donor (pyridine) that cannot promote decomposition via N–H activation pathways. Interception of this long-suspected species led to the proposal of “donorinduced” deactivation as a general decomposition pathway for Grubbs-class catalysts. Finally, the capacity of phosphine-free catalysts to overcome the shortcomings of the secondgeneration Grubbs catalysts was demonstrated, in a case study involving application of crossmetathesis (CM) to the synthesis of a high-value antioxidant. An efficient CM methodology was developed for the reaction of renewable essential-oil phenylpropenoids with vinyl acrylates. This work illustrates a new paradigm in sustainable metathesis. Rather than degrading unsaturated feedstocks via metathesis (a process that can be termed “metathe[LY]sis”), it demonstrates how metathesis with directly-functionalized olefins can be used to augment structure and function. From the perspective of organometallic chemistry and catalyst design, key comparisons built into this thesis are the effect of the NHC ligand (IMes vs. H2IMes) and its trans ancillary ligand on the efficient entry into catalysis; the susceptibility to nucleophilic attack of the alkylidene ligand (benzylidene vs. methylidene) vs. the metallacyclobutane; and the effect of replacing a phosphine ancillary ligand with a non-nucleophilic donor. From a practical standpoint, Chapter 2 brings new life to metathesis with the high-yield synthesis of the resting state species, Chapters 3 and 4 examine the deactivation, or death, of the methylidene complexes, and Chapter 5 establishes a new paradigm for olefin metathesis within the context of sustainable synthesis.
Keywords: Olefin Metathesis; Homogeneous Catalysis; Catalyst Deactivation